Economic Effects of Materials Policies: Combining an Applied General Equilibrium Model with Materials Flows - Patricia P.A.A.H. Kandelaars; Rob B. Dellink (Tinbergen Institute, 1997)
This study aims at integrating a materials flow model into an economic model, such that theeconomic effects of policies on the use materials and products can be analysed. Methods for studyingmaterials and product flows do not properly take into account economic, behavioural or policy aspects.But most economic models do not consider material flows explicitly.To analyse the economic effects an applied general equilibrium (AGE) model is used. The mainadvantage is that full direct and indirect effects of policies can be analysed. A disaggregated model isused to examine the effects of materials and product policies on various production sectors, householdsgroups, employment and the use of materials.The model is applied to metal flows in the Netherlands. The results show that the effects of aregulating levy on materials may be large for some production sectors, depending on where in theproduction process the levy is imposed. The basic metal industry and large metal using productionsectors may be negatively affected by metal levies. Positive effects of the levies occur for otherproduction sectors, for example the basic chemical industries and the petroleum refineries. In mostscenarios, the labour income households can improve their real income, whilst the households oftransfer recipients observe a fall in real income. However, for most production sectors and householdgroups the effects are small. No `double dividend' is found in the various scenarios.
Keywords: 330; Materials policies; materials flow analysis; applied general equilibrium (AGE); empirical modelling; Allgemeines Gleichgewicht; Metall; Rohstoffpolitik; Niederlande